2023
DOI: 10.3390/cancers15092448
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping the Pancreatic Cancer Microenvironment at Different Stages with Chemotherapy

Abstract: The dynamic tumor microenvironment, especially the immune microenvironment, during the natural progression and/or chemotherapy treatment is a critical frontier in understanding the effects of chemotherapy on pancreatic cancer. Non-stratified pancreatic cancer patients always receive chemotherapeutic strategies, including neoadjuvant chemotherapy and adjuvant chemotherapy, predominantly according to their physical conditions and different disease stages. An increasing number of studies demonstrate that the panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Similar to our findings, the study conducted by Víctor Sánchez-Margalet et al also reported that neoadjuvant chemotherapy leads to a reduction of NK cells, CD4 T cells (including Tregs cells) in peripheral blood of breast cancer (BRCA) patients, while CD8 T cells were decreased only in a minority of patients, which was consistent with our results [ 24 ]. Other studies also indicate that chemotherapy exerts a similar remodeling effect on T cell populations, thereby enhancing the ability to eliminate tumors [ [25] , [26] , [27] ]. Additionally, gene ontology (GO) analysis revealed that DEGs of T cell clusters were primarily enriched in multiple aspects, such as cell activation, adaptive immune response, and immune response to tumor cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, the study conducted by Víctor Sánchez-Margalet et al also reported that neoadjuvant chemotherapy leads to a reduction of NK cells, CD4 T cells (including Tregs cells) in peripheral blood of breast cancer (BRCA) patients, while CD8 T cells were decreased only in a minority of patients, which was consistent with our results [ 24 ]. Other studies also indicate that chemotherapy exerts a similar remodeling effect on T cell populations, thereby enhancing the ability to eliminate tumors [ [25] , [26] , [27] ]. Additionally, gene ontology (GO) analysis revealed that DEGs of T cell clusters were primarily enriched in multiple aspects, such as cell activation, adaptive immune response, and immune response to tumor cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In PC, there are a large number of stromal responses, which promote immune escape, tumor growth, and decrease parenchymal cells. 22 The targeted therapy drugs and newly discovered chemotherapeutic agents necessitate a representative study cohort and an appropriate pharmacogenomic platform. The preclinical PC PDX models are widely recognized as the gold standard as they are highly reliable and have significant predictive capabilities.…”
Section: Patient-derived Modelsmentioning
confidence: 99%